2020
DOI: 10.1002/cncr.33181
|View full text |Cite
|
Sign up to set email alerts
|

Patient and diagnostic intervals of survivors of sarcoma: Results from the SURVSARC study

Abstract: BACKGROUND: Patients diagnosed with sarcoma are hypothesized to experience a prolonged route to a cancer diagnosis. This route, the total interval, can be divided into a patient interval (the time from the appearance of symptoms to physician consultation) and diagnostic interval (time from the first consultation to diagnosis). In the current study, the authors investigated these intervals among survivors of sarcoma and identified factors associated with prolonged intervals. METHODS: A cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Over half (56%) of the rare cancer patients in this study reported diagnostic intervals of >1 month. The primary analysis of the diagnostic intervals of this SURVSARC study has been published previously [25]. Diagnostic intervals in common cancers vary greatly between different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Over half (56%) of the rare cancer patients in this study reported diagnostic intervals of >1 month. The primary analysis of the diagnostic intervals of this SURVSARC study has been published previously [25]. Diagnostic intervals in common cancers vary greatly between different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…The other patient characteristics were similar between the location groups (Table 1). The non-responder analyses have been published before, indicating a younger age at diagnosis and at study enrolment, and a lower social-economic status (SES) for non-responders [19]. 1)…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This heterogeneity of the disease was also reflected in HRQoL outcomes in German sarcoma patients and survivors [34]. These data show that the development of a single instrument is challenging, and it may not be the best option to meet the needs of academia and industry to assess the impact of new treatments [15,35].…”
Section: Introductionmentioning
confidence: 98%
“…Despite the effectiveness of treatments for sarcoma, the varying degrees of long-lasting and cumulative treatment side-effects and morbidity in a substantial number of patients contribute negatively to their overall outcome [8,14,15]. Information on survival only is insufficient to determine the net clinical (or true) benefit of a treatment for patients, and subjective patient-reported outcomes (PROs), including health-related quality of life (HRQoL), should be considered as well.…”
Section: Introductionmentioning
confidence: 99%